Trade with Endogenous Transportation Costs: The Value of LNG Exports - Atle Oglend; Petter Osmundsen; Tore Selland Kleppe (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper investigates the economic value of trade when prices of transportation services are endogenous to cross-market price spreads. This is relevant for liquefied natural gas (LNG) exports. LNG transportation capacity is limited in the short-run, and long lead-times are involved in extending the transportation infrastructure. We establish empirically that LNG transportation costs have been endogenous to regional gas prices spreads. As such, transportation service providers have been able to capture part of the price spread. We proceed to develop a method to value LNG exports under conditions of endogenous transportation costs and market integration. We use this method to quantify the effect of endogenous transportation costs on the value of LNG exports from the US to Japan. Our analysis shows that when transportation costs are correctly treated as endogenous, the LNG export benefit can drop by as much as 20-50% relative to the case of exogenous cost.
Keywords: F13; Q27; Q48; 330; LNG; natural gas; export; trade policy